METHODS USED BY ENGLISH DEPARTMENT STUDENTS IN TRANSLATING REPORT TEXT: A CONTENT ANALYSIS - Lina Anisah (Indonesian EFL Journal, 2022)
This research was conducted at 4th Semester Students of English Language Education Study Program of Sembilanbelas November University Kolaka. The objectives of this research were to find out the translation methods that used to translate a report text by 4th semester students and the most dominant translation method used to translate a report text by 4th semester students. Kinds of translation method in this research were word for word translation, literal translation, and free translation. The most dominant method used to translate a report text in this research was Literal Translation. The design of this research was a qualitative content analysis. The subject was 4th Semester Students of English Language Education Study Program of Sembilanbelas November University Kolaka. The data collection was conducted through documentation. The data of this research were taken from the students’ translation work. The instrument of this research was translation test. The data of students’ translation work were analyzed using content analysis. The findings showed that there were 435 sentences of students’ translation work which divided into three kinds of translation methods according to Newmark’s theory, namely word for word translation had 60 data with the percentage 14%. Literal translation had 304 data with the percentage 70%. The last free translation had 71 data with the percentage 16%. It showed that the most dominant translation method which was used by the students was literal translation that there were 304 or 70% data from 435 data of students’ translation work.Keywords: translation; translation method; and report text.